Physical Layer Framework for the Multi-Gigabit Copper-Fiber Access Networks. Issue 6 (2nd November 2018) - Strobel, Rainer
ABSTRACT: In future, Internet access speeds beyond 1 Gbit/s will be required, which is mainly provided by fiber connections in the fixed access network. A high-performance copper-based transmission technology can enable fiber to the building and fiber to the home installations in a cost-effective copper/fiber hybrid network. ITU has started a project for multi-gigabit copper access (MGfast), as a successor of the G.fast technology with the goal to provide symmetric services with 10 Gbit/s aggregated rate for each subscriber. Besides the use of higher bandwidth up to 424 MHz or 848 MHz, full duplex transmission with echo cancellation is another major improvement in MGfast. Line bonding and frequency bonding allow the use of the same physical layer architecture for different media types. This paper discusses network topologies for the hybrid network and technology options for copper transmission to achieve the desired rate and reach.